Morphological Processes Found in Umpasa and Umpama of Tobanese "Pesta Na Monding” - Maria Novesia Situmeang; Roma July Venny BR. Silalahi; Resperdiana Purba (Jurnal Ilmiah Wahana Pendidikan, 2021)
The title of this research is “Morphological Processes Found In Umpasa and Umpama of Tobanese "Pesta na Monding“.This paper discuss about how morphological process found in Tobanese language especially in umpasa and umpama on pesta na monding. The objectives firstly are to find kinds of morphological process of English words that are affixation, reduplication, compounding, and suppletion. The method is descriptive qualitative research. The data collection methods in this study were observation and interviews. Through this research we can find out the many morphological aspects of the process which apparently can form new words that also have different meanings from the original meanings.Overall, this study contributes to a deeper knowledge of morphosyntactic in lingustics, in addition to the attempt to explore and revitalize an Indonesian regional language.Keywords : morphological process, umpasa and umpama, Tobanese language